Candidate rejuvenating factor GDF11 and tissue fibrosis: friend or foe - Frohlich, Jan; Vinciguerra, Manlio (GeroScience, 2020)
Growth differentiation factor 11 (GDF11 or bone morphogenetic protein 11, BMP11) belongs to the transforming growth factor-β superfamily and is closely related to other family member-myostatin (also known as GDF8). GDF11 was firstly identified in 2004 due to its ability to rejuvenate the function of multiple organs in old mice. However, in the past few years, the heralded rejuvenating effects of GDF11 have been seriously questioned by many studies that do not support the idea that restoring levels of GDF11 in aging improves overall organ structure and function. Moreover, with increasing controversies, several other studies described the involvement of GDF11 in fibrotic processes in various organ setups. This review paper focuses on the GDF11 and its pro- or anti-fibrotic actions in major organs and tissues, with the goal to summarize our knowledge on its emerging role in regulating the progression of fibrosis in different pathological conditions, and to guide upcoming research efforts.
Keywords: Fibrosis; Aging; Growth Differentiation Factors; Animals; kostní morfogenetické proteiny; Bone Morphogenetic Proteins; zvířata; Mice; fibróza; stárnutí; růstové diferenciační faktory; myši